Fisherman settlement arrangement to area zero waste - Roswita Rensa Susanto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2016)
The quality of the environment in Gudang Lelang fishermen district is getting decrease because of trash problem. The purpose of the research is to know the appropriate form of the district’s arrangement as a problem solving of trash to be applied to Gudang Lelang fishermen as a Zero Waste district. The methods of data collection are observation, literature, and interview. The analysis performed covers environment, human and building which the result of the analysis is startegy for district planning.